P239 Is a pleural on-call service beneficial?. (15th November 2017) - Asciak, R; Hallifax, R; Mercer, RM; Corcoran, J; Wrightson, J; Hassan, M; Bradley, C; Psallidas, I; Rahman, NM
Abstract : Aim: To audit the pleural on-call service referrals and outcome. Method: Our unit instituted the provision of a "pleural phone" and pleural email service as a central point of contact for pleural related questions, both internally for our large Trust, and externally including local GPs, to facilitate a more open model of care, increase efficiency of the diagnostic pathway and prevent unnecessary admissions or procedures. All documented pleural phone (9 am-5 pm, Monday-Friday) and email (any time) referrals between March 2016-February 2017 were analysed. Results: 506 cases were discussed via email (n=257) or via phone calls (n=249), and this only included logged phone calls (mean 1.9 referrals per working day). This is an underestimation of the number of calls received because phone calls documented on the electronic patient record were not accessible and therefore not included. The number of cases discussed via email is not a reflection of the number of emails, as each case may have involved several emails. Table 1 shows the reasons for referral. The outcome of the referrals included advice (33.6%, n=170), advice and pleural clinic follow up (23.7%, n=120), advice and scheduling for a pleural procedure (42.7%, n=216). Of the 216 scheduled for procedures, 49.1% (n=106) were scheduled for a procedure by the pleural team (n=29 pleural one-stop-shop appointments for procedure and review), 49.1% (n=106) were scheduled for a procedure by the radiology team, 1.4% (n=3) were scheduled for an initial procedure by the radiology team (pleural fluid aspiration) then a further procedure by the pleural team (indwelling pleural catheter insertion(n=2), medical thoracoscopy(n=1)), 0.5% (n=1) were scheduled for bronchoscopy. An analysis of the referrals revealed that 22 unnecessary procedures and clinic appointments were avoided after discussion with the pleural team including new pleural outpatient referrals (n=4), follow up pleural outpatient appointment(n=10), pleural procedure appointment (n=5), referral to another clinic(n=2), CT scan(n=1). Advice given on the most appropriate investigation, such as advising large volume aspiration rather than chest drain insertion and hospital admission for a new undiagnosed pleural effusion, was not quantifiable in this retrospective study. Discussion: Pleural on-call service is beneficial and can help avoid unnecessary clinic and procedure list appointments.